2002
DOI: 10.1021/jf020279y
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Constituents of Uruguayan Propolis

Abstract: Eighteen flavonoids including two new compounds, four aromatic carboxylic acids, and eleven phenolic acid esters including one new compound were isolated and identified from the ethyl acetate soluble fraction of the 70% ethanol extract of Uruguayan propolis. The new compounds were elucidated as pinobanksin 3-(2-methyl)butyrate (1; recently reported in Usia, T.; Banskota, A. H.; Tezuka, Y.; Midorikawa, K.; Matsushige, K.; Kadota, S. J. Nat. Prod. 2002, 65, 673-676) pinobanksin 3-isobutyrate (2), and 2-methyl-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 49 publications
1
62
0
5
Order By: Relevance
“…3,4-Dimethoxycinnamic acid (d), pinobanksin 5-methyl ether (e), pinobanksin (f), cinnamylideneacetic acid (i), pinocembrin (j), benzyl caffeate (k), pinobanksin 3-acetate (l), cinnamyl caffeate (p), pinostrobin (q), and tectochrysin (r) were isolated from the ethanol extract of Uruguayan propolis (Kumazawa et al, 2002). Kaempferol (g), apigenin (h), chrysin (m) and galangin (o) were purchased from Extra Synthese (Genay, France).…”
Section: Methodsmentioning
confidence: 99%
“…3,4-Dimethoxycinnamic acid (d), pinobanksin 5-methyl ether (e), pinobanksin (f), cinnamylideneacetic acid (i), pinocembrin (j), benzyl caffeate (k), pinobanksin 3-acetate (l), cinnamyl caffeate (p), pinostrobin (q), and tectochrysin (r) were isolated from the ethanol extract of Uruguayan propolis (Kumazawa et al, 2002). Kaempferol (g), apigenin (h), chrysin (m) and galangin (o) were purchased from Extra Synthese (Genay, France).…”
Section: Methodsmentioning
confidence: 99%
“…The previously known substances 2 ,4 ,6 -trihydroxydihydrochalcone (2) (Crombie et al 1988;Hufford and Lasswell 1978), 2 ,6 ,4-trihydroxy-4 -methoxydihydrochalcone (3) (Hermoso et al 2003;Mabry et al 1975), 2 ,6 -dihydroxy-4 -methoxydihydrochalcone (4) (Hermoso et al 2003;Nilsson 1961), 5,7-dihydroxyflavanone [(2S)-pinocembrin] (5) (Bick et al 1972;Miyakado et al 1976), 2 ,6 -dihydroxy-4 ,4-dimethoxy dihydrochalcone (6) (Nilsson 1961) and (2R,3R)-3,5,7-trihydroxy-3-O-acetylflavanone (7) (Kumazawa et al 2002;Tomás-Barberán et al 1993), were identified by their physical (mp, [˛] D ) and spectroscopic ( 1 H and 13 C NMR and mass spectra) data, including NMR 2D-COSY, HSQC and HMBC experiments that allowed the unequivocal assignment of their structures.…”
Section: Identification Of Compounds 2-7mentioning
confidence: 99%
“…Existem várias metodologias descritas para a preparação de extratos de produtos naturais, visando o isolamento de seus constituintes químicos. Um dos métodos considerado o mais adequado para a análise químico-farmacológica de própolis é a preparação de extratos hidroalcoólicos (KUMAZAWA et al, 2002;DUARTE et al, 2003;SAWAYA et al, 2004;TRUSHEVA et al, 2004;UZEL et al, 2005;CASTRO et al, 2007;ALENCAR et al, 2007;SILVA et al, 2007). Park et al (1998) (CUSTÓDIO et al, 2000;MACIEJEWICZ, 2001;DUARTE et al, 2003;HAYACIBARA et al, 2005;ALENCAR et al, 2007).…”
Section: Estratégias Para a Obtenção De Compostos Puros E Biologicameunclassified
“…A princípio, é geralmente empregada a cromatografia em coluna aberta, com sílica-gel como fase estacionária (KUMAZAWA et al, 2002;TRUSHEVA et al, 2004;PICCINELLI et al, 2005;SILVA et al, 2005;TRUSHEVA et al, 2006;TEIXEIRA et al, 2006;OLDONI, 2007;AWALE et al, 2008), podendo ser adaptada para a técnica da coluna seca, na qual se gasta menos solvente e sílica (COLLINS; BRAGA; BONATO, 1997).…”
Section: Estratégias Para a Obtenção De Compostos Puros E Biologicameunclassified
See 1 more Smart Citation